ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV SDN 1 TEPAS PADA MASA PANDEMI COVID-19 - Anisah Mufidah; Safruddin; Muhammad Turmuzi (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
This study aims to determine the factors that cause learning difficulties in mathematics carried out during the covid-19 pandemic, to determine the efforts made by teachers in overcoming difficulties in learning mathematics. This type of research is qualitative research. The subjects in this study were teachers of grade 4 SDN 1 Tepas and 40 students of grade 4 SDN 1 Tepas. Data collection methods are interviews, questionnaires and documentation. The data obtained were then analyzed for the types of learning difficulties in mathematics, internal and external factors that cause difficulties in learning mathematics, the efforts that teachers can make in overcoming difficulties in learning mathematics carried out during the covid-19 pandemic. So from the data obtained, it can be concluded that the causes of learning difficulties in mathematics for grade 4 SDN 1 Tepas students during the COVID-19 pandemic were caused by internal factors and external factors that were directly related to students.